Recipient cell nuclear factors are required for reprogramming by nuclear transfer - Egli, Dieter (Company of Biologists, 2010)
Nuclear transfer allows the reprogramming of somatic cells to totipotency. The cell cycle state of the donor and recipient cells, as well as their extent of differentiation, have each been cited as important determinants of reprogramming success. Here, we have used donor and recipient cells at various cell cycle and developmental stages to investigate the importance of these parameters. We found that many stages of the cell cycle were compatible with reprogramming as long as a sufficient supply of essential nuclear factors, such as Brg1, were retained in the recipient cell following enucleation. Consistent with this conclusion, the increased efficiency of reprogramming when using donor nuclei from embryonic cells could be explained, at least in part, by reintroduction of embryonic nuclear factors along with the donor nucleus. By contrast, cell cycle synchrony between the donor nucleus and the recipient cell was not required at the time of transfer, as long as synchrony was reached by the first mitosis. Our findings demonstrate the remarkable flexibility of the reprogramming process and support the importance of nuclear transcriptional regulators in mediating reprogramming.